2015
DOI: 10.1080/1369183x.2014.1002200
|View full text |Cite
|
Sign up to set email alerts
|

Media Portrayals of Minorities: Muslims in British Newspaper Headlines, 2001–2012

Abstract: To better understand the public portrayal of minorities, we propose a new and systematic procedure for measuring the standing of different groups that relies on the tone of daily newspaper headlines containing the names of minority groups. This paper assesses the portrayal of Muslims in the British print media between 2001 and 2012, focusing especially on testing scholarly propositions that Muslims are depicted in a systematically negative way. We compare the tone of newspaper headlines across time and across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 37 publications
3
66
0
10
Order By: Relevance
“…The topics that Krämer and Schmidtke suggest Muslims might want explained, such as rights, values, and the justification of violence, are those journalists want explained as well. Studies on the representation of Islam and Muslims in Western news media have proliferated since the attacks on the World Trade Center and the Pentagon on 11 September 2001 (Poole 2002;Richardson 2004;Moore et al 2008;Baker et al 2013;Bleich et al 2015). Kerry Moore and colleagues studied a sample of UK coverage of Islam from 2000 to 2008 and found that two thirds of the stories focused "on Muslims as a threat (in relation to terrorism), a problem (in terms of differences in values) or both (Muslim extremism in general."…”
Section: Introductionmentioning
confidence: 99%
“…The topics that Krämer and Schmidtke suggest Muslims might want explained, such as rights, values, and the justification of violence, are those journalists want explained as well. Studies on the representation of Islam and Muslims in Western news media have proliferated since the attacks on the World Trade Center and the Pentagon on 11 September 2001 (Poole 2002;Richardson 2004;Moore et al 2008;Baker et al 2013;Bleich et al 2015). Kerry Moore and colleagues studied a sample of UK coverage of Islam from 2000 to 2008 and found that two thirds of the stories focused "on Muslims as a threat (in relation to terrorism), a problem (in terms of differences in values) or both (Muslim extremism in general."…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Muslims tend to be cast as outsiders and associated with terrorism, violence and security threats (e.g. Alsultany 2012; Bail 2012;Bleich et al 2015;Meer 2012;Petley and Richardson 2011). According to recent scholarship, the Canadian mainstream media do not seem to differ in this regard (Antonius 2013;Flatt 2013;Jasmine 2015;Kowalski 2013;Perigoe and Eid 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is an implicit hierarchy of worth, and perhaps a hierarchy of rationality, of religions, where Islam seems to be at the bottom (cf. Bleich, Stonebraker, Nisar, & Abdelhamid, 2015), being portrayed as a threat to liberal societies and rational thinking (cf. Huntington, 1996).…”
Section: Feared Consequences Of Becoming the Minoritymentioning
confidence: 99%